Abnormal meiotic recombination with complex chromosomal rearrangement in an azoospermic man. Issue 6 (June 2015) - Wang, Liu; Iqbal, Furhan; Li, Guangyuan; Jiang, Xiaohua; Bukhari, Ihtisham; Jiang, Hanwei; Yang, Qingling; Zhong, Liangwen; Zhang, Yuanwei; Hua, Juan; Cooke, Howard J.; Shi, Qinghua
Highlights Subject was azoospermic reciprocal translocation 46, XY, t(5;7;9;13) carrier. H&E stained testicular sections revealed no spermatids or sperm in the patient. TUNEL assay demonstrated apoptotic cells in testicular sections of translocation carrier. Increase in zygotene and decrease in the pachytene spermatocytes were observed in subject. Significant decrease in the recombination frequency of the translocation carrier